The Effects of Supplemental Feeding on Methane Emissions from Yak Grazing in the Warm Season - Wanhao Ma; Muhammad Irfan Malik; Alan D. Iwaasa; Hong Wang; Hongli Wang; Jinfen Yang; Binqiang Bai; Jianwu Jing; Guangwei Hu; Lizhuang Hao; Shujie Liu (Animals)
The yak industry constitutes a pivotal segment of livestock development across the Qinghai–Tibetan Plateau and adjacent pastoral regions. Existing studies have shown that supplemental feeding for grazing yaks significantly improves meat quality and growth performance, but its effect on enteric methane (CH4) emission from yaks has never been reported, so the present experiment aimed to investigate the effect of supplemental feeding of grazing yaks on CH4 emissions in three different periods of the warm season. Thirty male yaks were randomly assigned to two groups, with 15 yaks per group, The groups were designated as the grazing group (GR), with traditional grazing methods and with an initial body weight of 94.56 ± 3.9 kg, and the supplemental feeding group (GRS) with an initial body weight of 95.01 ± 4.1 kg, which received 1500 g/d of supplemental feed for 120 days. The methane emissions of the two groups were measured at the late regreening period (LRP), the greening-grass period (GGP), and the browning period (BRP) using the SF6 tracer method. The results showed that GRS increased (p < 0.01) the total DMI during warm season but decreased (p < 0.01) the forage intake at the LRP and GGP, resulting in a significantly reduced methane yield per kg of BW gain and per kg of DMD in warm-season grazing yaks (p < 0.01), a significantly reduced methane production per kg of DMI and methane energy to gross energy ratio in grazing yaks during the GGP (p < 0.05), and a similarly significantly decrease in methane production per kg of DMI and methane energy to gross energy ratio in grazing yaks during the BRP (p < 0.01). In conclusion, supplemental nutrition for grazing yaks during the warm season in alpine grasslands significantly enhances growth performance, reduces methane emissions, and improves dietary energy utilization efficiency.